Source and genesis of Ca-Cl type brines in Qaidam Basin, Qinghai-Tibetan Plateau: evidence from hydrochemistry as well as B and Li isotopes - Li, Yongshou; Pan, Tong; Li, Hongpu; Cheng, Huaide; Zhang, Pengcheng; Han, Wenhua; Li, Binkai; Yuan, Qin; Ma, Xuehai; Ma, Haizhou (Frontiers in Environmental Science, 2024)
Ca-Cl brine is a special water body with high mineralization endowed in oceanic ridges or basins. The deep part of the western Qaidam Basin is rich in Ca-Cl brine, which plays an important role in forming (MgSO4-deficient) potash deposits. For this type of brine in the Qaidam Basin, previous studies have tended to focus on its source tracing, but different carriers often led to different conclusions. At the same time, the genesis of Ca-Cl type brines in inland basins is still unclear. In essence, understanding the relatively abundant Ca sources for the formation of Ca-Cl brines in inland basins is lacking. In addition, the metallogenic model of this type of brine has not yet been established. In this study, through hydrochemical analysis and B, Li isotope tracing, we clarified that the main elements (Na, Cl, etc.) in the brines were mainly from the dissolution of existing evaporites inner the basin. At the same time, the trace elements in brines such as B, Li, etc., were mainly from the lixiviation when atmospheric rainfall infiltrated and interacted with ore-rich mother rocks along the basin-margin fracture system under certain temperature-pressure conditions, or the mixing with magmatic hydrothermal fluids. The above study shows that Ca-Cl type deep brines in the western part of the basin have a typical " binary structure " in terms of sources. In addition, the sources of Ca element in Ca-Cl brines were further discussed based on B and Li isotope studies, thus exploring a new genesis of Ca-Cl type brine formation in inland basins. Finally, integrating the above findings, the ore-forming model of this type of water body in the western part of the Qaidam Basin is systematically proposed. This study is of great reference value in understanding the genesis mechanism of Ca-Cl type brines in inland basins and is also of great practical significance in the prediction, exploration, and evaluation of this type of brine resource.